Effect of Garlic Supplementation on Performance, Carcass Traits and Blood Profile of Broiler Chicken - Khaidem, A.; Zuyie, R.; Haque, N.; Vidyarthi, V. K. (International Journal of Bio-resource and Stress Management, 2019)
An experiment was conducted to evaluate the feeding of garlic (Allium sativum L.)powder on the performance and blood profile of broiler chicken. A total of 120 day old Cobb-400 strains of broiler were distributed into four treatments groups with 30 birds in each treatment having five replicates of 6 birds each. The birds were reared in cages and were fed with diet supplemented with 0%, 0.25%, 0.50% and 0.75% of garlic powder. Feed and water was provided ad libitum and the experiment lasted for 42 days. The results had revealed that there was no significant (p>0.05) difference in body weight, gain in weight, feed intake and feed conversion efficiency, performance index, dressing percentage, carcass and organ weights due to different levels of garlic though the values were observed to be numerically better in garlic treated groups. Dietary supplementation of garlic had significant (p<0.05) effect on WBC and RBC and the values were observed to be maximum at the highest level of garlic (0.75%) and the least in control group (0%). Haemoglobin and differential white blood cells count were unaffected by garlic treatment. Economic analysis had shown that the groups fed with 0.25% and 0.05% garlic had the least cost of production and highest net profit kg-1 gain in weight. It was concluded that supplementation of garlic up to 0.75% did not have any adverse effect on the performance of broilers and garlic supplementation resulted in higher net return. The experiment was conducted as per CRD and the data was analysed using single way ANOVA.